Atrophy of myoepithelial cells in parotid glands of diabetic mice; detection using skeletal muscle actin, a novel marker. Issue 1 (1st February 2013) - Nashida, Tomoko; Yoshie, Sumio; Haga-Tsujimura, Maiko; Imai, Akane; Shimomura, Hiromi
Abstract : In mouse parotid glands, we found expression of skeletal muscle actin (actin‐α1) protein and mRNA. We isolated myoepithelial cells from the mouse parotid glands and investigated their actin‐α1 expression because smooth muscle actin (actin‐α2) has been used as a marker for myoepithelial cells. We used actin‐α1 expression to identify pathological changes in diabetic non‐obese diabetic (NOD; NOD/ShiJcl) mice—a mouse model for Sjögren's syndrome—and found myoepithelial cells to be decreased or atrophied in the diabetic state.